Intellectual Property Rights on Objects Created by Artificial Intelligence - Utkina, Maryna; Bondarenko, Olha; Chernadchuk, Tamara; Chernadchuk, Oleksandr (Law, State and Telecommunications Review, 2023)
[Purpose] The article aims to comprehensively analyze intellectual property rights concerning objects created by artificial intelligence. In particular, to identify and explore theoretical and methodological approaches to the definition of artificial intelligence; to study the process of implementation of artificial intelligence systems in the creation of intellectual property; describe the legal status of artificial intelligence; explore the main approaches to determining the authorship of objects created by artificial intelligence or with its help; to analyze the possibility of protection of objects created by artificial intelligence or with its use. [Methodology/Approach/Design] Several general and unique methods of scientific knowledge were used to achieve the goal and ensure the scientific objectivity and validity of its results. In particular, the work was based on the method of systems analysis (to develop a strategy for the study of legal regulation of the status of artificial intelligence); logical-semantic method (to determine the definitions in work); interpretation of legal norms (to clarify the content of relevant legal norms, as well as to establish the state of their practical application) and others. [Findings] The anthropological concept is the only possible concept that can protect the copyrights of persons involved in creating intellectual property rights and encourage them to develop further / use artificial intelligence. The author is recognized as an individual.